Pemantapan Ekonomi Masyarakat Melalui Skim Al-Rahnu - Norashikin, Ibrahim (2010)
The purpose of this study was to look at how the Islamic pawn or al-Rahnu into a micro-credit loan scheme which is vital for low-income earners to meet the immediate cash requirements to complete the project of economic and educational needs of children. Five objectives to be achieved by the researchers that the level of customer satisfaction with quality of service, the quality of services provided by the Islamic pawnshop, different levels of customer satisfaction Islam based on demographic factors, the relationship between service quality and customer satisfaction levels of service quality dimensions that influence the customer satisfaction. Population satisfaction survey of 156 customers using the service of al-Rahnu YAPElM Changlun and branches of Bank Jitra, Kedah using convenience sampling technique(Convenience Sampling). Data collected were analyzed using the program Statistical Package for Social Science (SPSS). The study has shown that customer satisfaction is high on the score of 67.9% regression analysis. Empathy factor, reliability and compliance are critical factors in this study. In conclusion, the customer is satisfied with the quality of services provided by al-Rahnu YAPEIM and Bank Rakyat branches Jitra.